Large-scale synthesis of stable mesoporous black TiO2 nanosheets for efficient solar-driven photocatalytic hydrogen evolution via an earth-abundant low-cost biotemplate. Issue 56 (24th May 2016) - Zhang, Kaifu; Zhou, Wei; Zhang, Xiangcheng; Qu, Yang; Wang, Lei; Hu, Weiyao; Pan, Kai; Li, Mingxia; Xie, Ying; Jiang, Baojiang; Tian, Guohui
Abstract : Stable mesoporous black anatase TiO2 nanosheets (MBTNs) are synthesized via an earth-abundant low-cost biotemplate method combined with an ethanediamine encircling process, and exhibit excellent solar-driven photocatalytic hydrogen generation. Abstract : Stable mesoporous black anatase TiO2 nanosheets (MBTNs) are synthesized via an earth-abundant low-cost biotemplate method combined with an ethanediamine encircling process, and subsequent high-temperature calcinations and surface hydrogenation. The MBTNs, which can be synthesized on a large scale with a low cost, are composed of Ti 3+ in frameworks and surface disorders. In this case, the employment of ethanediamine encircling plays a vital role in fabricating the stable MBTNs, and not only favors high-temperature hydrogenation (600 °C), but also retains the mesoporous network as well as inhibiting the anatase-to-rutile phase transformation and grain growth. The resultant MBTNs possess a relatively high surface area of ∼74 m 2 g −1, and large pore size and pore volume of ∼10 nm and 0.15 cm 3 g −1, respectively. The MBTNs, with a narrow bandgap of ∼2.85 eV, can extend the photoresponse from the ultraviolet to visible light region, and exhibit an excellent solar-driven photocatalytic hydrogen evolution rate (∼165 μmol h −1 0.05 g −1 ), which is about twice as high as that of pristine mesoporous TiO2 nanosheets (∼82 μmol h −1 0.05 g −1 ). This efficient solar-driven photocatalytic hydrogen evolution is ascribed to the synergistic effects of the highly crystalline, ultrathin 2D mesoporous structure of Ti 3+ in frameworks and surface disorders.